An Efficient Metadynamics-Based Protocol To Model the Binding Affinity and the Transition State Ensemble of G-Protein-Coupled Receptor Ligands - Saleh, Noureldin; Ibrahim, Passainte; Saladino, Giorgio; Gervasio, Francesco Luigi; Clark, Timothy (Journal of Chemical Information and Modeling, 2017)
A generally applicable metadynamics scheme for predicting the free energy profile of ligand binding to G-protein-coupled receptors (GPCRs) is described. A common and effective collective variable (CV) has been defined using the ideally placed and highly conserved Trp6.48 as a reference point for ligand GPCR distance measurement and the common orientation of GPCRs in the cell membrane. Using this single CV together with well-tempered multiple-walker metadynamics with a funnel-like boundary allows an efficient exploration of the entire ligand binding path from the extracellular medium to the orthosteric binding site, including vestibule and intermediate sites. The protocol can be used with X-ray structures or high-quality homology models (based on a high-quality template and after thorough refinement) for the receptor and is universally applicable to agonists, antagonists, and partial and reverse agonists. The root-mean-square error (RMSE) in predicted binding free energies for 12 diverse ligands in five receptors (a total of 23 data points) is surprisingly small (less than 1 kcal mol(-1)). The RMSEs for simulations that use receptor X-ray structures and homology models are very similar.

A Three-Site Mechanism for Agonist/Antagonist Selective Binding to Vasopressin Receptors - Saleh, Noureldin; Saladino, Giorgio; Gervasio, Francesco L.; Haensele, Elke; Banting, Lee; Whitley, David C.; Santos, Jana Sopkova-De Oliveira; Bureau, Ronan; Clark, Timothy (Angewandte Chemie International Edition, 2016)
Molecular-dynamics simulations with metadynamics enhanced sampling reveal three distinct binding sites for arginine vasopressin (AVP) within its V-2-receptor (V2R). Two of these, the vestibule and intermediate sites, block (antagonize) the receptor, and the third is the orthosteric activation (agonist) site. The contacts found for the orthosteric site satisfy all the requirements deduced from mutagenesis experiments. Metadynamics simulations for V2R and its V1aR-analog give an excellent correlation with experimental binding free energies by assuming that the most stable binding site in the simulations corresponds to the experimental binding free energy in each case. The resulting three-site mechanism separates agonists from antagonists and explains subtype selectivity.
Keywords: G-protein coupled receptors; hormones; metadynamics; molecular dynamics; receptors

Can Simulations and Modeling Decipher NMR Data for Conformational Equilibria? Arginine-Vasopressin - Hänsele, Elke; Saleh, Noureldin; Read, Christopher M.; Banting, Lee; Whitley, David C.; Clark, Timothy (Journal of Chemical Information and Modeling, 2016)
Arginine vasopressin (AVP) has been suggested by molecular-dynamics (MD) simulations to exist as a mixture of conformations in solution. The H-1 and C-13 NMR chemical shifts of AVP in solution have been calculated for this conformational ensemble of ring conformations (identified from a 23 mu is molecular-dynamics simulation). The relative free energies of these conformations were calculated using classical metadynamics simulations in explicit water. Chemical shifts for representative conformations were calculated using density-functional theory. Comparison with experiment and analysis of the results suggests that the H-1 chemical shifts are most useful for assigning equilibrium concentrations of the conformations in this case. C-13 chemical shifts distinguish less clearly between conformations, and the distances calculated from the nuclear Overhauser effect do not allow the conformations to be assigned clearly. The H-1 chemical shifts can be reproduced with a standard error of less than 0.24 ppm (<2.2 ppm for C-13). The combined experimental and theoretical results suggest that AVP exists in an equilibrium of approximately 70% saddlelike and 30% clinched open conformations. Both newly introduced statistical metrics designed to judge the significance of the results and Smith and Goodman's DP4 probabilities are presented.

Differences between G-Protein-Stabilized Agonist-GPCR Complexes and their Nanobody-Stabilized Equivalents - Saleh, Noureldin; Ibrahim, Passainte; Clark, Timothy (Angewandte Chemie International Edition, 2017)
Protein nanobodies have been used successfully as surrogates for unstable G-proteins in order to crystallize G-protein-coupled receptors (GPCRs) in their active states. We used molecular dynamics (MD) simulations, including meta-dynamics enhanced sampling, to investigate the similarities and differences between GPCR-agonist ternary complexes with the alpha-subunits of the appropriate G-proteins and those with the protein nanobodies (intracellular binding partners, IBPs) used for crystallization. In two of the three receptors considered, the agonist-binding mode differs significantly between the two alternative ternary complexes. The ternary-complex model of GPCR activation entails enhancement of ligand binding by bound IBPs: Our results show that IBP-specific changes can alter the agonist binding modes and thus also the criteria for designing GPCR agonists.
Keywords: allosterism; G-protein-coupled receptors; ligand binding; molecular dynamics; transmembrane receptors

Identification of Two Distinct Sites for Antagonist and Biased Agonist Binding to the Human Chemokine Receptor CXCR3 - Milanos, Lampros; Saleh, Noureldin; Kling, Ralf; Kaindl, Jonas; Tschammer, Nuska; Clark, Timothy (Angewandte Chemie International Edition, 2016)
The chemokine receptor CXCR3 is a G protein-coupled receptor that conveys extracellular signals into cells by changing its conformation upon ligand binding. We previously hypothesized that small-molecule allosteric CXCR3-agonists do not bind to the same allosteric binding pocket as 8-azaquinazolinone-based negative allosteric modulators. We have now performed molecular-dynamics (MD) simulations with metadynamics enhanced sampling on the CXCR3 system to refine structures and binding modes and to predict the CXCR3-binding affinities of the biased allosteric agonist FAUC1036 and the negative allosteric modulator RAMX3. We have identified two distinct binding sites; a shallow and a second deeper pocket to which the biased allosteric agonist FAUC1036 and negative allosteric modulator RAMX3 bind, respectively.
Keywords: allosterism; membrane proteins; molecular dynamics; protein structures; signal transduction

Investigating allosteric effects on the functional dynamics of beta 2-adrenergic ternary complexes with enhanced-sampling simulations - Saleh, Noureldin; Saladino, Giorgio; Gervasio, Francesco Luigi; Clark, Timothy (Chemical Science, 2017)
Signalling by G-protein coupled receptors usually occurs via ternary complexes formed under cooperative binding between the receptor, a ligand and an intracellular binding partner (a G-protein or beta-arrestin). While a global rational for allosteric effects in ternary complexes would be of great help in designing ligands with specific effects, the paucity of structural data for ternary complexes with beta-arrestin, together with the intrinsic difficulty of characterizing the dynamics involved in the allosteric coupling, have hindered the efforts to devise such a model. Here we have used enhanced-sampling atomistic molecular-dynamics simulations to investigate the dynamics and complex formation mechanisms of both beta-arrestin- and G(s)-complexes with the beta 2-adrenergic receptor (ADRB2) in its apo-form and in the presence of four small ligands that exert different allosteric effects. Our results suggest that the structure and dynamics of arrestin-ADRB2 complexes depend strongly on the nature of the small ligands. The complexes exhibit a variety of different coupling orientations in terms of the depth of the finger loop in the receptor and activation states of ADRB2. The simulations also allow us to characterize the cooperativity between the ligand and intracellular binding partner (IBP). Based on the complete and consistent results, we propose an experimentally testable extended ternary complex model, where direction of the cooperative effect between ligand and IBP (positive or negative) and its magnitude are predicted to be a characteristic of the ligand signaling bias. This paves the avenue to the rational design of ligands with specific functional effects.

Molecular mechanisms of biased and probe-dependent signaling at CXC-motif chemokine receptor CXCR3 induced by negative allosteric modulators - Brox, Regine; Milanos, Lampros; Saleh, Noureldin; Baumeister, Paul; Buschauer, Armin; Hofmann, Dagmar; Heinrich, Markus; Clark, Timothy; Tschammer, Nuska (Molecular Pharmacology, 2018)